2015
DOI: 10.1177/0018726715569855
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation discrimination in the United Kingdom’s labour market: A field experiment

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 54 publications
(122 reference statements)
5
102
0
6
Order By: Relevance
“…Acquisti and Fong (2015) submitted identical résumés to the employers but manipulated the information in candidates' online profiles on professional and social networks. Drydakis (2015) was the only study to send résumés of real job applicants.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acquisti and Fong (2015) submitted identical résumés to the employers but manipulated the information in candidates' online profiles on professional and social networks. Drydakis (2015) was the only study to send résumés of real job applicants.…”
Section: Methodsmentioning
confidence: 99%
“…Hireability ratings of gay applicants were not significantly related to evaluators' perception of legality of sexual orientation discrimination (Horvath & Ryan, 2003 * ) and, after controlling for background characteristics, nor to existence of state antidiscrimination laws (Barron, 2009 * ). In terms of call-back rates, Drydakis (2015) observed that gay applicants were more disadvantaged in companies without a written commitment to equal opportunity (p ࣘ .01) than in companies with such commitment. Also Tilcsik (2011) found that county-and state-level antidiscrimination laws reduce negative bias against gay men (p ࣘ .05), but this effect was not significant when controlling for state-level attitudes toward lesbians and gay men.…”
Section: Effect Of Local Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…factory/manual workers) are perceived as blue-collar jobs, while jobs in services (such as in restaurant/sales and offices) are perceived as pink-collar and white-collar jobs. Finally, by focusing on both sexes, we can account for how gender might affect access to vacancies (Drydakis 2015).…”
Section: Design Of the Studymentioning
confidence: 99%
“…Drydakis' (2015) research identified that participation in gay and lesbian university students' unions negatively affected participants' workplace prospects, with the 17 probability of gay or lesbian applicants receiving an invitation to interview 5% lower than their heterosexual counterparts. Related to this, European research (Formby, 2014) suggests that some students may hide their LGBT-related activities or activism whilst at university, in order to (try) to gain employment: Issues about presentation of self or identity were specifically raised in relation to interview dress and performance:…”
Section: Facilities and Service Provision On Campusmentioning
confidence: 99%